Comparison of peritoneal dialysis catheter insertion techniques: Peritoneoscopic, radiological and laparoscopic : A single‐centre study. Issue 5 (May 2016) - Sun, Tina Y‐T; Voss, David; Beechey, Denise; Lam‐Po‐Tang, Michael
Abstract: Background: Our centre introduced peritoneoscopic insertion of peritoneal dialysis (PD) catheter by nephrologists as a new method in August 2009 for its potential benefits. Aim: The aim of this study was to compare perioperative complications and catheter survival of three techniques: peritoneoscopic, surgical and radiological techniques within a single dialysis centre. Method: This study used retrospective analysis of all PD catheter inserted from 1 August 2009 to 31 July 2013 within Counties Manukau DHB, Auckland, New Zealand. Results: During the study period, 293 PD catheters were inserted, 84 (29%) peritoneoscopic (P), 140 (48%) surgical (S) and 69 (23%) radiological (R). Total duration of follow‐up was 5848 catheter‐months, with median follow‐up of 17 months. There was no difference in perioperative exit‐site infections and overall early infections. There was however increased overall perioperative complications in P compared with R (HR 2.08; P  < 0.05), predominantly from catheter removal within 60 days. Although there was no difference observed in first catheter 1‐year and overall survival between insertion techniques, there was poorer complication‐free survival comparing P to S (HR 1.82, P  = 0.001) but not to R. Analyses of the latter cohort of P confirmed improvement in catheter survival compared with an earlier cohort and to other insertion techniques. Conclusion: Peritoneoscopic PD catheter insertion is demonstrated to be a suitable alternative technique. As with any new procedure, 'learning curve' effects and development of operator expertise need to be taken into consideration. Summary at a Glance: This retrospective study compares perioperative outcomes and peritoneal dialysis catheter survivals between three different catheter insertions techniques–peritoneoscopic, laparoscopic surgical and radiological. Nephrologist‐led peritoneoscopic insertion has been demonstrated to be a safe alternative with many benefits.